Experimental and numerical investigation on the thermal performance of triple tube heat exchanger equipped with different inserts with WO3/water nanofluid under turbulent condition - Tiwari, Arun Kumar; Javed, Summaiya; Öztop, Hakan Fehmi; Said, Zafar; Pandya, Naimish S. (Elsevier France-Editions Scientifiques Medicales Elsevier, 2021)
A novel curve tube design called Triple Tube Heat Exchanger was investigated to identify the thermofluidic characteristics in the current paper. This research analysis comprises of both computational fluid dynamics and experimental results. A three-dimensional computational fluid dynamics model was developed using Ansys R19.1 (fluent) research package, and the k-epsilon model is used to realize the thermofluidic characteristics. In this new design, an additional tube is introduced between a double concentric tube heat exchanger. The complete analysis is done under consideration of turbulent fluid to fluid heat transfer conditions. The influence of different thermal parameters such as overall heat transfer and effectiveness were the main points of research interest by using WO3/water nanofluid with different novel inserts like twisted tape, rib, and porous plate. The thermodynamic effect of nanofluid was considered under the concentration range of 0.5%-3.0%. The computational fluid dynamics method is used to simulate the process, and experimental data is used to validate it. The result shows that the maximum overall heat transfer rate and effectiveness were 1767.91 W/m(2)K, 1702.71 W/m(2)K, and 1.86, 1.79, respectively, at 1% optimized volume concentration with WO3/water nanofluid by using rib type insert during experimental and computational fluid dynamics methods, respectively. The maximum thermal performance factor by using nanofluid in the rib type insert was observed at 0.75. The study shows an enhancement of 11.84%, 12.38%, and 14.56%, 14.30% in overall heat transfer and effectiveness by using a rib-type insert for both experimental and computational fluid dynamics methods, respectively, in comparison to without using inserts. There was also a progressive decrement in friction factor during the increment in mass flow rates.
Keywords: Triple tube heat exchanger; Nanofluids; Inserts; CFD; Thermal characteristics